The Relationship Between Student Perceptions of Guidance and Counseling Services - Putri, Monica Febi Fatricia; Harahap, Ade Chita Putri (Universitas Islam Negeri Raden Intan Lampung, 2023)
Guidance and counseling services are activities carried out through direct or face-to-face eye contact to help individuals who are experiencing problems so that these individuals can understand themselves and their environment, choose and make decisions, and can be responsible for the various problems themselves. . Related to this competency, guidance and counseling teachers or counselors manage programs including compiling programs, implementing programs, and evaluating guidance and counseling programs to help students develop optimally according to student needs. This research was conducted at SMA Negeri 1 Bandar Khalipah, Serdang Bedagai Regency. The method used in this research is correlational descriptive quantitative research. The data were sourced from the students who were the research samples, namely at each level a sample of 120 students was taken at SMA Negeri 1 Bandar Khalipah, Serdang Bedagai Regency. As for how to collect data using a Likert scale instrument. The steps taken in data analysis are data description and hypothesis testing. Based on the test results, it can be seen that there is a significant relationship between perception and attitude, this is evidenced by the sig coefficient = 0.000 <0.05 and the Pearson correlation coefficient = 0.556. So the results of the study indicate that there is a significant positive relationship between views about the professional competence of counselors with the aim of providing student guidance and counseling services